2019
DOI: 10.1002/ijc.32181
|View full text |Cite
|
Sign up to set email alerts
|

GITR ligation enhances functionality of tumor‐infiltrating T cells in hepatocellular carcinoma

Abstract: No curative treatment options are available for advanced hepatocellular carcinoma (HCC). Anti‐PD1 antibody therapy can induce tumor regression in 20% of advanced HCC patients, demonstrating that co‐inhibitory immune checkpoint blockade has therapeutic potential for this type of cancer. However, whether agonistic targeting of co‐stimulatory receptors might be able to stimulate anti‐tumor immunity in HCC is as yet unknown. We investigated whether agonistic targeting of the co‐stimulatory receptor GITR could rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…We also found that five kinds of immune cells were significantly positively related to the signature, including activated mast cells, M0 macrophages, resting dendritic cells, and activated memory CD4 T cells. It has been reported that tumor infiltration by T and B cells can improve the survival rate of patients with HCC (24)(25)(26)(27). Macrophages in HCC are linked to a good prognosis of HCC, and low immune cell infiltration in hepatocellular carcinoma is associated with the presence of neutrophils, NK cells and resting mast cells (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that five kinds of immune cells were significantly positively related to the signature, including activated mast cells, M0 macrophages, resting dendritic cells, and activated memory CD4 T cells. It has been reported that tumor infiltration by T and B cells can improve the survival rate of patients with HCC (24)(25)(26)(27). Macrophages in HCC are linked to a good prognosis of HCC, and low immune cell infiltration in hepatocellular carcinoma is associated with the presence of neutrophils, NK cells and resting mast cells (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…For HCC, a proof-of-concept pre-clinical experiment demonstrated that agonistic targeting of GITR with a GITR ligand or activating GITR antibody amplified the ex-vivo activity of tumor-infiltrating T-cells in HCC. This was illustrated by CD8+ T cell proliferation and granzyme B expression [105]. Targeting GITR and PD1 may improve anti-cancer T-cell in some patients and GITR is a promising immunotherapy target in HCC.…”
Section: Role Liver Directed Therapies Associated With Immunotherapymentioning
confidence: 99%
“…Recently, PD-1 blockade and activation of GITR could synergistically induce the activation of T cells [163]. In addition, agonistic targeting of GITR was shown to augment TIL functionality in hepatocellular carcinoma [164].…”
Section: Immunotherapeutic Approaches Against Cancermentioning
confidence: 99%